STUDY OF PHYTOCHEMICAL COMPOUND CONTENT AND ANALGESIC ACTIVITY OF ETHANOL EXTRAK OF CELERY LEAF (Apium graveolens L.) WRITHING TEST METHOD: STUDY OF PHYTOCHEMICAL COMPOUND CONTENT AND ANALGESIC ACTIVITY OF ETHANOL EXTRAK OF CELERY LEAF (Apium graveolens L.) WRITHING TEST METHOD - Rosa Juwita Hesturini; Fathul Hidayatul Hasanah; Dwi Wahyuni; Briandini Dwi Astuti; Anis Anggrayni (JURNAL PHARMA BHAKTA, 2026)
Background: The celery plant (Apium graveolens L.) belongs to the Apiaceae family and is one of the vegetable commodities that is widely used for flavoring and decorating dishes with various health benefits. Objective: This study aims to determine the content of phytochemical compounds and analgesic activity of celery leaves. Through a systematic review article. Method: The research method with systematic literature review was carried out by searching for articles or journals related to phytochemical compound content and analgesic activities of celery. which had been published in journals. Literature search was conducted in April-May 2021 through Google Scholar, then journals were selected based on exclusion and inclusion criteria. Conclusions: The inclusion criteria, namely journals published last 5 years, the journal discusses the content of phytochemical compounds and analgesic activity of ethanol extract of celery leaves using the writhing test method. And as for the exclusion criteria, the data in the journal is incomplete and the journal does not discuss the celery plant. Based on the results of a systematic literature review of 5 published journals indicate that celery plant contains phytochemicals flavonoid compounds, tannins, saponins flavor-glucoside (apiin), apigenin and have analgesic activity.